THE COMPARISON OF INHIBITORY EFFECT BETWEEN ANTISEPTIC SOAP WITH BETEL LEAF EXTRACT (Piper betle Linn) ON THE GROWTH OF Escherichia coli - Tiroyo, Amelia Julianty; Munir, Muhammad Ardi; Hutasoit, Gina Andhyka (Medika Tadulako: Jurnal Ilmiah Kedokteran Fakultas Kedokteran dan Ilmu Kesehatan, 2016)
Background. Infectious diseases are still a major cause of morbidity and mortality in developing countries. One of the most commonly way to prevent the spread of infectious diseases is washing hands with antiseptic soap. Recently, lifestyle back to nature is widely used by the public which is they using herbs. Betel leaves can be used as an antibacterial because it contains 4.2% of essential oil. Escherichia coli bacteria are the primary pathogens that cause infections in humans.Method. This research is a true laboratorial experimental research post test only control group. The test material used are LB soap, DT soap, 25% and 50% betle leaf extract, 1% povidone iodine as positive control and distilled water as negative control. Each treatment was replicated four times. Antibacterial effect determine by the extent of the inhibition zone formed.Result. The result shows that the average of inhibition highest test material is LB soap is 49,875 mm, followed by 50%, 25 % betel leaf extract and DT soap with each zone of inhibition formed is 27,05 mm, 23,525 mm, and 22,25 mm. For the positive control group had inhibitory zone is 29,525 mm, and the negative control was not formed inhibition zones. Statistical test results using Kruskal-Wallis had significance value p<0,05, which means there is a significant difference from the sixth treatment given to the growth of Escherichia coli.Conclusion. There are differences between the inhibition of antiseptic soap and betle leaf extract (Piper betle Linn) to the growth of Escherichia coli.Â Keyword. Antiseptic soap, Betel leaf extract (Piper betle Linn), Escherichia coli, antibacterial, inhibitory effect